PENGUJIAN KOROSI UAP ASAM TEMPERATUR TINGGI LAPISAN ZINC PADA SUBSTRAT BAJA KARBON - Muhammad Rizky; Eni Sugiarti M.Eng; Edi Sanjaya, M.Si (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Geothermal Power Plant is one of the solution of nowdays energy demand problem. But there are problems occur on the Geothermal Power Plant-it is the pipeing system made from carbon steel which is fragile to be corroded. Has been done corrosion test of the zinc-coated carbon steel-which is available in market-by hydrochloric acid (HCl) 37% in the room temperature (28 Â°C) and 300 Â°C. After the corrosion test, samples were measured their mass change to calculate the corrosion rate predictions, then characterized by X-Ray Diffractometer (XRD). The result showed that zinc is able to protect carbon steel substrate from corrosion on the room temperature, meanwhile on the high temperature it can not protect carbon steel substrate from corrosion.Keywords: Geothermal Power Plant, Corrosion, Zinc, Temperature.